2010
DOI: 10.1093/annhyg/meq070
|View full text |Cite
|
Sign up to set email alerts
|

Improving Flow and Spillage Characteristics of Range Hoods by Using an Inclined Air-Curtain Technique

Abstract: The current study developed a new type of range hood, which was termed an 'inclined air-curtain range hood', in order to improve the flow and performance of the conventionally used wall-mounted range hood. The flow characteristics and oil mist spillages of air-curtain and conventional range hoods under the influences of both a mannequin presence and a simulated walk-by motion were experimentally examined. The study examined flow patterns by using a laser-light-sheet-assisted smoke-flow visualization technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The draft effect was a kind of continuous disturbance of airflow in kitchens. It was different from the effect of walk-by mentioned by Huang et al 18 , 21 ) . Chen et al 19 ) presented the containment of conventional range hoods operating under the effect of a cross draft.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The draft effect was a kind of continuous disturbance of airflow in kitchens. It was different from the effect of walk-by mentioned by Huang et al 18 , 21 ) . Chen et al 19 ) presented the containment of conventional range hoods operating under the effect of a cross draft.…”
Section: Introductionmentioning
confidence: 69%
“… 18 ) investigated the performance of a wall-mounted range hood with laser-assisted flow visualization in static conditions (the draft of the environment was controlled) and dynamic conditions (humans walking by). A novel design of a range hood was reported by Huang et al 20 , 21 ) . A range hood with the installed inclined air-curtain was called the inclined air-curtain range hood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 ). For comparison, the data for the IAC and conventional range hoods were quoted from Huang et al 20 , 21 ) . The conventional range hood has a very low robustness.…”
Section: Resultsmentioning
confidence: 99%
“…Huang et al . 20 , 21 ) represented an inclined air-curtain (IAC) range hood which was designed by combining a suction slot installed at the hood and a plane jet arranged at the front part of the countertop to form a backward-inclined push-pull air curtain. They showed that the IAC range hood has higher performance than the conventional range hoods under both the static and dynamic tests.…”
Section: Introductionmentioning
confidence: 99%